2004
DOI: 10.1002/eji.200324336
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic dendritic cell subsets in the mouse

Abstract: The CD11c(+) cell population in the non-parenchymal cell population of the mouse liver contains dendritic cells (DC), NK cells, B cells and T cells. In the hepatic CD11c(+) DC population from immunocompetent or immunodeficient [recombinase-activating gene-1 (RAG1)(-/-)] C57BL/6 mice (rigorously depleted of T cells, B cells and NK cells), we identified a B220(+) CD11c(int) subset of 'plasmacytoid' DC, and a B220(-) CD11c(+) DC subset. The latter DC population could be subdivided into a major, immature (CD40(lo)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 34 publications
9
63
0
Order By: Relevance
“…Based on prior work showing a potent ability of DCs to stimulate NK T cells (14)(15)(16)(17)(18)(19)31), we first focused on these cells. To evaluate the role of DCs as APCs for NK T cells in vivo, we used a Tg mouse model that allows for transient depletion of DCs (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior work showing a potent ability of DCs to stimulate NK T cells (14)(15)(16)(17)(18)(19)31), we first focused on these cells. To evaluate the role of DCs as APCs for NK T cells in vivo, we used a Tg mouse model that allows for transient depletion of DCs (22).…”
Section: Discussionmentioning
confidence: 99%
“…Fujii et al (14) showed that DCs loaded with ␣-GalCer and adoptively transferred into na ve mice stimulated a better NK T cell response in vivo than that stimulated by injection of free compound. Other studies have demonstrated the ability of ␣-GalCer to induce maturation of both splenic and hepatic DCs in vivo (15,16), and others have shown the importance of DCs as sources of ␣-GalCer-induced IL-12 (17)(18)(19).…”
mentioning
confidence: 99%
“…Lastly, in the report of Jomantaite et al (14), liver DCs were categorized based on the relative expression of CD8␣ and CD11b initially, but for functional analysis the myeloid and lymphoid fractions were combined as a CD11c intermediate B220 Ϫ group. In their analysis, the hepatic DCs were divided into two groups based solely on the expression of B220, and, consistent with our findings, they showed that bulk B220 Ϫ splenic DCs were more stimulatory.…”
Section: Discussionmentioning
confidence: 99%
“…[78] . Further, the presence of CD8α + CD11b -and CD8α -CD11b + DCs has been reported [78] . The continuous exposure of resident APCs with the bacterial cell wall derived LPS promotes the induction of CD4 regulatory T cells and may explain the dominance of IL-10 in the liver [79,80] .…”
Section: Cd11cmentioning
confidence: 99%